Scaling up: microbiome manipulation for climate change adaptation in large organic vineyards - Pino, Carlos; Griffon, Diego (Frontiers in Sustainable Food Systems, 2024)
Regenerative agriculture offers important solutions to the enormous challenges that the climate crisis poses on food production. However, there are doubts about the possibility of implementing many of these solutions in a particularly important sector: the large scale. This paper addresses the issue, presenting examples of large-scale vineyard soil microbiome manipulation in Chile. The South American country has strongly faced the effects of climate change during the last decade and the organic viticulture sector is actively seeking strategies to adapt to the new climatic reality. Here the results of 4 experiments under real production conditions are shown. The experiments were designed to assess the effects of adding various microbial consortia to the soil on key agronomic parameters. Successful as well as unsuccessful cases are presented, allowing discussion of some conditions under which the microbiome manipulation can be expected to have positive effects. It was found that under good management conditions, incorporating effective microorganisms has positive effects on important production parameters (yield, root and vegetative growth). However, when fields yields are trending downward for prolonged periods, the incorporation of effective microbial consortia (e.g., antagonistic fungi, nutrient-fixing and nutrient-solubilizing bacteria) does not have a positive effect on the vineyard trend immediately. Similarly, even in favorable conditions the positive effects cannot be expected to be expressed in the short term (i.e., in just a few months). Therefore, its use should be conceived as a long-term strategy, not as an immediate solution to urgent management problems.